2013
DOI: 10.1021/sc300132x
|View full text |Cite
|
Sign up to set email alerts
|

Highly and Fully Water Dilutable Sustainable Microemulsions with Dibasic Esters as Oil Phase

Abstract: In this study, we show a strategy of formulating highly and fully water dilutable sustainable microemulsions with dibasic esters as oil pseudophase. First, dimethyl or diethyl DBEs with different numbers of carbon atoms between the ester functions (succinate C2, glutarate C3, and adipate C4) or DBE blends and a surfactant–cosurfactant melt consisting of sodium dodecylsulfate and 1-pentanol with a constant weight ratio of 1:2 are used. We investigated the extent of the realms of existence of homogeneous single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The microemulsions assembled from monochain surfactants need the usage of cosurfactants indispensably. Medium length alkyl alcohols with four or five carbon atoms are generally considered to be suitable as cosurfactants, which promote the formation of microemulsions accompanied by synergistic effects. , However, the massive usage of cosurfactants with high cost generally limits their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The microemulsions assembled from monochain surfactants need the usage of cosurfactants indispensably. Medium length alkyl alcohols with four or five carbon atoms are generally considered to be suitable as cosurfactants, which promote the formation of microemulsions accompanied by synergistic effects. , However, the massive usage of cosurfactants with high cost generally limits their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, oil-in-water (O/W) "macroemulsions" are heterogeneous, opaque, and thermodynamically unstable systems in which oil droplets will coalesce, eventually leading to phase separation. In contrast, oil-in-water "microemulsions" have nano-sized oil droplets and are macroscopically homogeneous and thermodynamically stable systems; they also have some distinguishing physicochemical properties: optical transparency, isotropy, and low viscosity [18]. The present work focuses on the fire-suppression capability of ferrocene-containing microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…DBE is known as a low-risk green solvent that is derived from biomass which is biodegradable. 17,18 DBE solution provides an environment beneficial to the formation of stereocomplex crystals. On the basis of previous studies, the thermally induced technique is reported to be an easy scalable method, which separates the mixture solution into two phases (polymer-rich/polymer-lean phase) either by exposing the solution to an immiscible solvent or by cooling the solution below its solubility temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we reported the preparation of complete high molecular-weight (HMW) SCPLA using the thermally induced technology with dibasic ester (DBE) as medium. DBE is known as a low-risk green solvent that is derived from biomass which is biodegradable. , DBE solution provides an environment beneficial to the formation of stereocomplex crystals. On the basis of previous studies, the thermally induced technique is reported to be an easy scalable method, which separates the mixture solution into two phases (polymer-rich/polymer-lean phase) either by exposing the solution to an immiscible solvent or by cooling the solution below its solubility temperature. This whole system reduced the temperature of preparation of SCPLA, which effectively inhibited the PLA degradation and reduced the energy consumption.…”
Section: Introductionmentioning
confidence: 99%